Modelling Tidal Flow Hydrodynamics of Sunda Strait, Indonesia - Munawir Bintang Pratama; Vengatesan Venugopal; Harman Ajiwibowo; Juventus Welly Ginting; Franto Novico (Marine Science Department Diponegoro University, 2020)
In the past years, Indonesian people put more attention to Sunda Strait located between Java and Sumatra Islands, one of the busiest straits occupied with residential, recreational, fisheries, transportation, industrial and mining activities. Previous works on numerical modelling of tidal flow hydrodynamics of the Sunda Strait have resulted in good agreement against field data; however, the calibration of the models used was not described in detail. This paper presents the process of setting up the model, extensive calibration, validation and prediction of tidal currents for the Sunda Strait. A two-dimensional tidal-driven model is constructed using Delft3D, an open-source developed by Deltares. Four different bathymetry datasets, four different boundary condition configurations, and various bed roughness values are used, and their suitability in predicting tidal water level and current are investigated. It is found that changing the bathymetry and boundary conditions improve the model validation significantly. GEBCO_2019 bathymetry dataset outperforms the Batnas, even though it has a coarser resolution. For boundary conditions, the combination of water level and current velocity results in a better validation compares to using water level or current velocity only. However, the bed roughness shows an insignificant influence in predicting tidal conditions. The averaged current velocity is lower at the Southern than the Northern side of the strait due to a larger cross-section, consequence of deeper water. High tidal currents of magnitude around 2 m.s-1 are seen at the bottleneck of the strait.